Lymphoma dissemination is a pathological hallmark for malignant progression of B-cell lymphoma - Li, Xiaoxi; Jiang, Yong; Qian, Hui (Frontiers in Immunology, 2023)
Extranodal lymphoma occurs in one-third of lymphoma patients and is a key indicator of the international prognostic index, associated with unfavorable outcomes. Due to the lack of ideal models, the causes and characteristics of extranodal lymphoma are greatly underexplored. Recently, we observed a high incidence of extranodal lymphoma in two types of mouse models with tropism for the brain and kidneys. These findings prompt us to rethink the pathological progression of lymphoma colonization in lymph nodes and non-lymphoid organs. Nodal lymphoma, primary extranodal lymphoma and secondary extranodal lymphoma should be biologically and clinically distinctive scenarios. Based on the observations in mouse models with extranodal lymphoma, we propose that lymphoma dissemination can be seen as lymphoma losing the ability to home to lymph nodes. The pathological process of nodal lymphoma should be referred to as lymphoma homing to distinguish it from benign hyperplasia. Lymphoma dissemination, defined as a pathological process that lymphoma can occur in almost any part of the body, is a key pathological hallmark for malignant progression of B-cell lymphoma. Reshaping cellular plasticity is a promising strategy to allow transformed cells to homing back to lymph nodes and re-sensitize tumor cells to treatment. From this perspective, we provide new insights into the pathological progression of lymphoma dissemination and its inspiration on therapeutic interventions. We believe that establishing extranodal lymphoma mouse models, identifying molecular mechanism governing lymphoma dissemination, and developing therapies to prevent lymphoma dissemination will become emerging topics for fighting relapsed and refractory lymphoma.